1985
DOI: 10.1037/0033-2909.97.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Fiedler's Contingency Theory of Leadership: An application of the meta-analysis procedures of Schmidt and Hunter.

Abstract: The present review was designed to apply the Schmidt and Hunter meta-analysis procedures to the available literature on Fiedler's Contingency Theory of Leadership. In the present instance, this involved the quantification of the variance in correlations between leader style and performance that can be explained by sampling error. To the extent that the variance in these results across studies can be explained by sampling error, moderator variables, including situational favorability, would be unnecessary theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(86 citation statements)
references
References 46 publications
0
83
0
3
Order By: Relevance
“…This indicates that the study requires the examination of moderator effect. Peters et al [60] has suggested that the moderator effect should be performed if the sampling error variance is less than 60% of the observed variance. For every organizational attribute that showed a sampling error variance of less than 60% of observed variance, we introduced four moderating conditions and performed a meta-analysis.…”
Section: Meta Analysis Proceduresmentioning
confidence: 99%
“…This indicates that the study requires the examination of moderator effect. Peters et al [60] has suggested that the moderator effect should be performed if the sampling error variance is less than 60% of the observed variance. For every organizational attribute that showed a sampling error variance of less than 60% of observed variance, we introduced four moderating conditions and performed a meta-analysis.…”
Section: Meta Analysis Proceduresmentioning
confidence: 99%
“…In the 1960s, drawing on a third strand of research that described the actual behavior of leaders (e.g., Bales, 1950;Lippitt & White, 1943;Stogdill, 1974), Fiedler (1965Fiedler ( , 1971) introduced an interactionist model; the leadership effectiveness of a particular behavioral style is contingent on the favorability of the situation to that behavioral style. Fiedler's contingency theory is generally reasonably well supported (e.g., Strube & Garcia, 1981) despite some continuing controversy (e.g., Peters, Hartke, & Pohlmann, 1985).…”
mentioning
confidence: 99%
“…This theory predicts that task-motivated leaders perform best in highand low-control situations while relationship-motivated leaders perform best in moderate-control situations (see meta-analyses by Strube & Garcia, 1981;Peters, Hartke, & Pohlmann, 1985). Experience increases situational control since job methods become more routine and outcomes more predictable (see Fiedler, 1966;1967;Fiedler & Garcia, 1987).…”
Section: Linking Cognitive Resource Theory and Other Contingency Theomentioning
confidence: 99%